POLICY STRATEGY INTEGRATED DEVELOPMENT OF TOURISM DESTINATIONS IN SOUTH SULAWESI - Andi Cudai Nur (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
This study aims to determine the policy strategy partnership integrated the development of tourism destinations in South Sulawesi. This study uses a combination of research methods sequential explanatory model or designs a method that combines a combination of quantitative and qualitative research methods in series, wherein the first phase of the research carried out by using quantitative methods and in the second stage with qualitative methods. This type of research used in this study is mixed methods research (mixed methods). The study is a mixed-methods research approach that combines or associate the form of qualitative and quantitative form. This approach involves philosophical assumptions, approaches the application of qualitative and quantitative, and mixing (mixing) of both approaches in a single study. Policy in the form of Tourism Development Master Plan (RIPP) used as a guide in directing, fostering, developing, and controlling the development of the tourism sector in Bulukumba, preferably stems from the source of the problem and must be enforceable through local regulation.